2021
DOI: 10.1155/2021/6698673
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Peck Formula to Predict Ground Surface Settlement of Twin Tunnels in Low Permeability Soil

Abstract: Accurate prediction of surface settlement induced by tunnel excavation is significant for preventing damage to existing structures under complex geological conditions. The Peck formula is currently considered as an efficient solution for surface settlement prediction. This paper proposes a modified Peck formula considering geological conditions to improve the accuracy of surface settlement prediction of twin tunnels. The asynchronization of the sinking rate and stability of the vault settlement and surface set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Wang et al [7] used Peck's formula to fit tunnel surface settlement data obtained in Beijing and discussed the effects of construction methods, tunnel burial depth, support stiffness, and other factors, on the empirical parameters of the formula and then gave a correction formula for the empirical parameters. Han et al [8] suggested values for the empirical parameters in the Peck formula by studying tunnel surface settlement data obtained in Beijing and Shanghai and pointed out the limitations of the applicability of the Peck formula to ultra-shallow buried tunnels. In addition, many other predictive methods have been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [7] used Peck's formula to fit tunnel surface settlement data obtained in Beijing and discussed the effects of construction methods, tunnel burial depth, support stiffness, and other factors, on the empirical parameters of the formula and then gave a correction formula for the empirical parameters. Han et al [8] suggested values for the empirical parameters in the Peck formula by studying tunnel surface settlement data obtained in Beijing and Shanghai and pointed out the limitations of the applicability of the Peck formula to ultra-shallow buried tunnels. In addition, many other predictive methods have been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Peck [15] explained that the settlement trough caused by tunnels can be fitted using a Gaussian function. The prediction of ground settlement deformation has evolved from two-dimensional to three-dimensional deformation and from single-track tunnels to multi-track tunnels [16,17] based on the continuous supplementation and modification of empirical formulas. Although empirical methods have been widely accepted in the tunneling industry, they lack a theoretical basis.…”
Section: Introductionmentioning
confidence: 99%
“…Shield tunneling is considered as a commonly used technology for tunnel construction. The difficulty of applying shield tunneling in urban areas with prosperous business districts nearby is in controlling the ground deformation caused by overexcavation [1][2][3][4][5][6]. Over-excavation and the strata loss of shield construction may be caused by the gap between soil and the lining, since the diameter of the shield shell is larger than the diameter of the lining.…”
Section: Introductionmentioning
confidence: 99%
“…Tunnel construction will inevitably induce varying degrees of ground movement and result in ground surface settlement. Many studies on the prediction of ground deformation in tunnel construction have been carried out by using empirical methods [4,[8][9][10][11][12], analytical methods [13,14], and numerical methods [15][16][17][18]. Empirical and analytical methods are more suitable for simple excavation applications, which do not take complex construction situations and existing structures into account.…”
Section: Introductionmentioning
confidence: 99%